STUDENT-CENTERED AND INTERACTIVE TEACHING IN MEDICAL UNIVERSITIES - Raxmonova Feruza; Maksudova Malika; Nadirova Yulduz (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract In recent years, medical education has undergone significant transformation due to rapid advancements in science, technology, and healthcare systems. Traditional teacher-centered instructional models are increasingly being replaced by student- centered and interactive teaching approaches that emphasize active learning, critical thinking, and practical competence. This article examines the concept of student- centered and interactive teaching in medical universities, explores commonly used interactive methods, and analyzes their impact on students’ academic performance, clinical skills, and professional development. The study highlights the importance of implementing innovative pedagogical strategies to improve the quality of medical education and better prepare future healthcare professionals for real-world challenges.